Percutaneous trans‐abdominal external looped needle with two holes in the trocar sheath for port‐site closures in difficult obese cases. Issue 4 (25th July 2016) - Lasheen, Ahmed E; Salem, Ayman; Abd Elaal, Salah; Elsheweal, Abd Elhafez; Osman, Gamal; Alkilany, Mohammed; Ibrahim, Amr
Abstract: Introduction: Port closure is essential after successful laparoscopic surgery to prevent incisional hernia. However, good fascial closure still represents a problem, especially in obese patients and when the port wound is oblique. We report a novel technique for port‐site closures in such cases. Methods: This study involved 67 obese patients who underwent laparoscopic surgery. We used a novel technique for port‐site closure that employed a looped needle passed through two holes in the port sheath. Results: The method was used in 67 patients (45 laparoscopic cholecystectomies, 22 laparoscopic hernia repairs), with a mean BMI of 35.7 kg/m 2 . No intraoperative incidents or port‐site hernias were reported during follow‐up (mean, 22 months). Conclusion: Our procedure is safe, easy, and effective for fascial port site closures, especially in cases of difficult obese patients and oblique port wounds.